From 'natural selection' to 'survival of the fittest': On the significance of Spencer's refashioning of Darwin in the 1860s. (May 2014) - Offer, John
This article examines what Spencer meant by his expression 'survival of the fittest' and its status in the explanation of change. It shows how in his Principles of Biology the expression was introduced in connection with his discussion of Darwin's mechanism of species change, 'natural selection', which he wished to incorporate into his all-embracing theory of evolution. The analysis demonstrates through textual examination that the relationship between the expressions 'natural selection' and 'survival of the fittest' was not, as is often assumed, one of equivalence, but that it embodied intellectually significant modifications of Darwin's position not acknowledged within references, themselves accurate enough, to Spencer's well-known preference for the inheritance of acquired characteristics over 'chance variations'. The article then discusses how Spencer applied what he understood by 'survival of the fittest' to the explanation of social change, as presented in his foundational contribution to sociology, The Principles of Sociology .